Process evaluation of a primary healthcare validation study of a culturally adapted depression screening tool for use by Aboriginal and Torres Strait Islander people: study protocol. Issue 11 (3rd November 2017) - Farnbach, Sara; Evans, John; Eades, Anne-Marie; Gee, Graham; Fernando, Jamie; Hammond, Belinda; Simms, Matty; DeMasi, Karrina; Hackett, Maree
Abstract : Introduction: Process evaluations are conducted alongside research projects to identify the context, impact and consequences of research, determine whether it was conducted per protocol and to understand how, why and for whom an intervention is effective. We present a process evaluation protocol for the Getting it Right research project, which aims to determine validity of a culturally adapted depression screening tool for use by Aboriginal and Torres Strait Islander people. In this process evaluation, we aim to: (1) explore the context, impact and consequences of conducting Getting It Right, (2) explore primary healthcare staff and community representatives' experiences with the research project, (3) determine if it was conducted per protocol and (4) explore experiences with the depression screening tool, including perceptions about how it could be implemented into practice (if found to be valid). We also describe the partnerships established to conduct this process evaluation and how the national Values and Ethics: Guidelines for Ethical Conduct in Aboriginal and Torres Strait Islander Health Research is met. Methods and analysis: Realist and grounded theory approaches are used. Qualitative data include semistructured interviews with primary healthcare staff and community representatives involved with Getting it Right. Iterative data collection and analysis will inform a coding framework. Interviews will continue until saturation of themes is reached, or all participants are considered. Data will be triangulated against administrative data and patient feedback. An Aboriginal and Torres Strait Islander Advisory Group guides this research. Researchers will be blinded from validation data outcomes for as long as is feasible. Ethics and dissemination: The University of Sydney Human Research Ethics Committee, Aboriginal Health and Medical Research Council of New South Wales and six state ethics committees have approved this research. Findings will be submitted to academic journals and presented at conferences. Trial registration number: ACTRN12614000705684 .